2018
DOI: 10.1103/physreva.98.062306
|View full text |Cite
|
Sign up to set email alerts
|

Masking quantum information in multipartite scenario

Abstract: Recently, Kavan Modi et al. found that masking quantum information is impossible in bipartite scenario. This adds another item of the no-go theorems. In this paper, we present some new schemes different from error correction codes, which show that quantum states can be masked when more participants are allowed in the masking process. Moreover, using a pair of mutually orthogonal Latin squares of dimension d, we show that all the d level quantum states can be masked into tripartite quantum systems whose local d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 27 publications
0
52
0
Order By: Relevance
“…Following the work of Modi et al, Li et al proposed quantum information masking schemes with multiparticle entangled states [4]. It has been proved that quantum information carried on a arbitrary qubit state |ψ α = α 0 |0 + α 1 |1 , where α = (α 0 , α 1 ), can be masked by the following mapping operations:…”
Section: Quantum Information Masking Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the work of Modi et al, Li et al proposed quantum information masking schemes with multiparticle entangled states [4]. It has been proved that quantum information carried on a arbitrary qubit state |ψ α = α 0 |0 + α 1 |1 , where α = (α 0 , α 1 ), can be masked by the following mapping operations:…”
Section: Quantum Information Masking Schemesmentioning
confidence: 99%
“…The masking process is completed by unitary operations called maskers which can map single-particle states to entangled states. Afterwards, Li et al proposed quantum information masking schemes by using multi-particle entangled states [4]. Quantum information masking has potential applications in entanglement-based quantum cryptography by hiding classical information in entangled states [3].…”
Section: Introductionmentioning
confidence: 99%
“…Many meaningful works on this topic have been published [11][12][13][14][15][16]. In [17], authors shows that qudit information masking can be accomplished in 2d-qudit or three-qudit system which employed the quantum orthogonal Latin squares [18]. Afterwards, this scenario was generalized to multipartite quantum information masking in multipartite system with the development of k−uniform states [19] which can be obtained from orthogonal arrays [20], Latin squares [21,22], quantum error correcting codes [23] et al…”
Section: Introductionmentioning
confidence: 99%
“…Based on this theorem, Ghosh et al [24] considered two special kinds of quantum states with orthogonal and non-orthogonal basis states to obtain the masking conditions. Li and Wang [25] presented some schemes different from error correction codes and showed that quantum states can be masked when more participants are allowed in the masking process. Then Han et al [26] further explored the relationship between quantum multipartite maskers (QMMs) and quantum error-correcting codes (QECCs).…”
Section: Introductionmentioning
confidence: 99%